Development of a 3D-Printed Dosing Platform to Aid in Zolpidem Withdrawal Therapy - Silke Henry; Lien De Vadder; Milan Decorte; Susanna Francia; Magali Van Steenkiste; Jan Saevels; Valérie Vanhoorne; Chris Vervaet (MDPI AG, 2021)
The long-term use of benzodiazepine receptor agonists (BZRAs) is associated with multiple side effects, such as increased sedation, hangover or an elevated risk of dependency and abuse. Unfortunately, the long-term use of BZRAs is reaching worrying intake rates, and therefore, the need for action is high. It was demonstrated already that the overall willingness of patients for deprescription increased when a slow dose reduction scheme with the possibility for dose increase, if needed, is employed. The current study aims to develop a flexible dosing platform of zolpidem hemitartrate (ZHT) to facilitate such withdrawal therapy. As this is the first report on the extrusion and 3D printing of ZHT, its thermal behaviour and sensitivity towards photolytic degradation was characterised. It was shown that ZHT possesses multiple polymorphs and was especially prone to oxidative photolysis. Next, a variety of immediate release polymers (Eudragit EPO, Kollidon VA64, Kollidon 12PF and Soluplus) were blended and extruded with Polyox WSR N10 to investigate their feedability and printability by mechanical and rheological analysis. The addition of PEO was shown to enable printing of these brittle pharmaceutical polymers, although the processing temperature was deemed critical to avoid surface defects on the resulting filaments. An EPO(70)PEO(30) system was selected based on its suitable mechanical properties and low hygroscopicity favoring ZHT stability. The matrix was blended with 1% or 10% API. The effect of certain printing parameters (caplet size, nozzle diameter, % overlap) on dissolution behaviour and caplet weight/dimensions/quality was assessed. A flexible dosing platform capable of delivering <1 mg and up to 10 mg of ZHT was created. Either caplet modification (incorporation of channels) or disintegrant addition (Primojel, Explotab, Ac-Di-Sol, Primellose and Polyplasdone-XL) failed to achieve an immediate release profile. This study provides the first report of a 3D-printed flexible dosing platform containing ZHT to aid in withdrawal therapy.